Development of Project-Based Learning E-Modules with Local Wisdom on Bojonegoro Bananas (Musa Spp.) to Improve Creative Thinking Skills - Purnamasari, Ita Septia; Rahayu, Yuni Sri; Yuliani (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
The ability to generate innovative ideas is a key competency required in 21st-century education; however, Indonesian students’ creative thinking skills remain relatively low. This study aims to develop a Project-Based Learning (PjBL)-based e-module integrated with the local wisdom of Bojonegoro bananas (Musa spp.) to enhance senior high school students’ creative thinking skills on the topic of plant tissues. Employing a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate), the study was conducted from February to October 2025. The results indicate that the local wisdom of Bojonegoro bananas is highly relevant as a contextual learning resource, with community perception and appreciation scores exceeding 85%. The developed e-module achieved a high level of validity (average score = 3.78) and demonstrated strong practicality based on readability, implementation, and student response assessments. Furthermore, effectiveness testing using a paired-sample t-test revealed a significant improvement in students’ creative thinking skills, supported by moderate to high N-Gain scores. These findings imply that integrating local wisdom through a PjBL-based e-module can serve as an effective pedagogical strategy to foster creative thinking, contextual learning, and meaningful engagement, and can be recommended for broader implementation within the Merdeka Curriculum and similar educational contexts.